(untitled) (Revista Cocar, 2023)
Este artigo relata a experiência vivenciada durante a Semana Mundial do Brincar, cujo desafio foi planejar e desenvolver propostas de experimentação na área de Ensino de Ciências para a Educação Infantil. Devido à escassez de estudos, ações e trabalhos voltados para a educação científica de crianças são fundamentais pois apresentam os desafios relacionados aos cuidados técnicos essenciais no meio acadêmico e em normas de segurança. O texto discutiu a necessidade de conciliar a preservação da integridade física com a forma natural das crianças de aprender, interagir e conhecer o mundo ao tocar, provar e cheirar. Além disso, destacou a importância da promoção da alfabetização científica na Educação Infantil como uma perspectiva a ser considerada para a reflexão e o aprimoramento das práticas de experimentação científica nesse contexto. Palavras-chave: Semana Mundial do Brincar; Experimentação; Educação Infantil. Abstract This article describes the experiences during World Play Week, which involved the challenge of planning and developing experimentation proposals in the discipline of Science for Children’s Education. Due to the lack of studies, activities and projects with the goal of providing children with science education are instrumental, as they present challenges related to key technical aspects surrounding academia and safety standards. The article discusses the need to preserve bodily integrity while also allowing children to learn, interact and experience the world through the most natural ways they know how, which is touching, tasting, and smelling. In addition, the article also emphasizes the importance of promoting scientific literacy in Children’s Education as a potential perspective in order to reflect on and improve scientific experimentation practices in this context. Keywords: World Play Week; Experimentation; Children’s Education.